Progress in the production of hydrogen energy from food waste: A bibliometric analysis. (22nd July 2022) - Sridhar, Adithya; Ponnuchamy, Muthamilselvi; Senthil Kumar, Ponnusamy; Kapoor, Ashish; Xiao, Leilei
Abstract: The exponential increase in food waste generation has prompted the scientific community to convert it into value-added resources. Hydrogen energy provides a sustainable option to fossil fuels due to its purity, high energy content, with no emissions other than water vapor. Combining the two aspects, a bibliometric analysis was performed for the conversion of food waste to hydrogen energy to evaluate the research trends based on literature in the Scopus database over the last two decades. The cluster analysis supported with the visualization tool aided in conducting a systematic study revealing growing themes and hot issues. The results showed a growing interest in the conversion of food waste to hydrogen energy research with the number of publications increasing by nearly 50 times in the last two decades. Comprehensive journals like the International Journal of Hydrogen Energy were most popular in publishing articles contributing to almost 30% in the research area. The country-wise analysis revealed that China accounted for more than 25% of the articles published followed by South Korea and India while the USA dominated in terms of the number of citations. Lastly, keyword cluster analysis revealed five major research hotspots for future discussion. The study concludes that further perspectives on fuel delivery, environmental impacts, and social acceptance could aid in positive developments in the biohydrogen energy industry. Graphical abstract: Image 1 Highlights: Bibliometric analysis shows future trends in food waste to hydrogen energy research. Author keyword analysis aids in outlining research hotspots for future discussion. Hydrogen production methods and food waste treatments were the prime themes. China and USA contributed to highest publications and citations respectively. Emphasis is needed on efficient commercialization, delivery and social acceptance.